KAJIAN POPULASI MIKROBIA RHIZOSPHERE DARI TANAMAN JAGUNG DI BEBERAPA TINGKAT PERMUKAAN AIR SALURAN DRAINASE DI KECAMATAN RASAU JAYA, KABUPATEN KUBU RAYA - Triyana, Sutarman Gafur Sulakhudin (Fakultas Pertanian Universitas Tanjungpura, 2019)
ABSTRACT This study aims to study the population of microorganisms (bacteria and fungi) on peat soil planted with maize with different water depths in Rasau Jaya Umum Village, Rasau Jaya District, Kubu Raya Regency. This research was conducted in Rasau Jaya Umum Village, Rasau Jaya District, Kubu Raya District. Observations were made on land planted with corn plants. Furthermore, this research was conducted at the Soil Biology and Biotechnology Laboratory, Faculty of Agriculture, Tanjungpura University. This research takes place from March to August 2017, namely from land preparation to harvest. Soil samples used are disturbed soil samples, which are carried out according to the depth of the drainage water surface. Samples were taken when the plants were harvested and samples were taken around the roots of each row of plants. Variables observed were: number and type of bacteria, number and type of fungi, moisture content and soil porosity, C/N ratio of soil, soil pH value, soil temperature, maturity of peat, bulk density.The results showed that the type and number of bacteria and fungi in the study area on the land after planting were more than the number and type of bacteria on the location before planting. The moisture content and porosity of the soil at the location of the study showed that the higher the porosity of the soil, the lower the water content in the soil. The ratio of C / N ratios in all study locations has very high criteria. The research location with 30 cm drainage water depth has the highest C / N ratio at a sample depth of 30-60 cm. The pH value of the soil at the study site is very acidic. The type of soil belongs to the type of hemic peat. The highest soil temperature value at a location with a drainage water depth of 60 cm with a sample depth of 0-15 cm. Keywords: Bacteria, Corn, Fungi, Peat, Drainage